The investigation of the properties of solar cells based on Kazakhstan silicon - И. Клиновицкая; С. Плотников; Д. Калыгулов; Ф. Лэ (Қарағанды университетінің хабаршысы. Физика сериясы)
The study of the properties of solar cells is a relevant topic since the development of solar energy corresponds to the global trend and the course of the Government of the Republic of Kazakhstan on the transition to a «green» economy. Various properties of solar cells such as resistivity and surface resistance, carrier lifetime, reflectivity, quantum efficiency, directly affect the efficiency of solar cells. This paper is devoted to obtaining and comprehensive study of solar cells manufactured on the basis of the Kazakhstani silicon of «solar» quality. The study applied: a method of microwave detected photoconductive decay (μ-PCD), four probe methods for measuring resistance, methods for spectrometric analysis of reflection, transmission and photoluminescence coefficients, scanning electron microscopy, and methods for analyzing current-voltage characteristics. The mastered methods of solar cells production are described. A modification of the standard Back Surface Field (BSF) cell line to the Passivated Emitter and Rear Cell (PERC) line has been proposed.